Combination of serum CST1 and HE4 for early diagnosis of endometrial cancer - Wenhui Zhong; Yunliang Liu; Liangming Zhang; Wanzhen Zhuang; Jianlin Chen; Zhixin Huang; Yue Zheng; Yi Huang (PeerJ, 2023)
Purpose Optimal serological biomarkers have been absent for the early diagnosis of endometrial cancer, to date. In this study, we aimed to define the diagnostic performances of individual and combined detection of serum cysteine protease inhibitor 1 (CST1) with traditional tumor markers, including glycated antigen 125 (CA125) and human epididymis protein 4 (HE4), in patients with early-stage endometrial cancer (EC). Methods The performances of individual and combined detection of serum CST1, HE4, and CA125 were evaluated by enzyme-linked immunosorbent assay (ELISA) and chemiluminescent immunoassay, respectively. A training data set of 67 patients with early EC, 67 patients with endometrial benign lesion (EBL), and 67 healthy controls (HC) was used to develop a predictive model for early EC diagnosis, which was validated by an independent validation data set. Results In the training data set, serum CST1 and HE4 levels in the early EC group were significantly higher than in EBL/HC groups (P < 0.05), while there was no significant difference of serum CA125 level between the early EC and EBL/HC groups (P > 0.05). Serum CST1 and HE4 exhibited areas under the curve (AUC) of 0.715 with 31.3% sensitivity at 90.3% specificity, and 0.706 with 23.9% sensitivity at 95.5% specificity, respectively. Combined detection of serum CST1 and HE4 exhibited an AUC of 0.788 with 49.3% sensitivity at 92.5% specificity. The combination of serum CST1 and HE4 showed promise in diagnosis. Conclusion CST1 is a prospective serological biomarker for early EC diagnosis, and the combination of CST1 and HE4 contributes to the further improvement in the diagnosis of patients with early-stage EC.